2019
DOI: 10.3390/nu11061318
|View full text |Cite
|
Sign up to set email alerts
|

The Consumption of Alcoholic Beverages and the Prevalence of Cardiovascular Diseases in Men and Women: A Cross-Sectional Study

Abstract: Associations between alcohol consumption and the prevalence of cardiovascular diseases have been the subject of several studies for a long time; however, the presence and nature of any associations still remain unclear. The aim of the study was to analyze the associations between the consumption of alcoholic beverages and the prevalence of cardiovascular diseases in men and women. The data of 12,285 individuals aged 37–66 were used in the analysis. Multiple logistic regression models were utilized to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…A cross-sectional study with 12,285 individuals aged 37-66 reported that the daily consumption of alcohol beverages (from 0.1 to 15.0 g) was inversely related to the development of hypertension in women (OR 0.67, 95%CI 0.59-0.75, p < 0.001). In contrast, this relation was not observed for men [52]. Moreover, in a cohort study published in 2010, Halanych et al described the relationship between five different categories of alcohol intake and the incidence of hypertension.…”
Section: Hypertensionmentioning
confidence: 97%
See 1 more Smart Citation
“…A cross-sectional study with 12,285 individuals aged 37-66 reported that the daily consumption of alcohol beverages (from 0.1 to 15.0 g) was inversely related to the development of hypertension in women (OR 0.67, 95%CI 0.59-0.75, p < 0.001). In contrast, this relation was not observed for men [52]. Moreover, in a cohort study published in 2010, Halanych et al described the relationship between five different categories of alcohol intake and the incidence of hypertension.…”
Section: Hypertensionmentioning
confidence: 97%
“…Many factors have been associated with the development of hypertension, such as an elevated body mass index, occupation, socioeconomic status, tobacco use, abdominal obesity, physical activity, and alcohol consumption, among others [5,48,51]. Many studies have reported a positive, dose-dependent association between alcohol intake and hypertension, showing the J-shaped curve also described for overall cardiovascular effects [5,16,19,22,[52][53][54][55][56]. Excessive alcohol consumption accounts for about 16% of cases of hypertension worldwide [5,57].…”
Section: Hypertensionmentioning
confidence: 99%
“…26 Smoking prevalence ranges from 18.1% to 42%, 29 and the prevalence of tobacco consumption was found to be 9% to 67%. 30 Many studies show that light to moderate drinking could be protective against heart diseases, [31][32][33] but other studies show the contrast evidence related to alcohol consumption and risk of heart diseases. 34,35 In our study, the percentage of nonvegetarian is more than vegetarians.…”
Section: Discussionmentioning
confidence: 99%
“…An unhealthy diet, on the other hand, would promote the onset of these diseases [19][20][21][22][23][24]. Almost all of studies on the impact of specific foods, nutrients, and drinks as well as dietary patterns on cardiovascular health [25][26][27][28][29][30][31] have been conducted in populations in developed countries. Aside from some recent data which give some fragmentary information on some populations in developing countries [32,33] data's are almost nonexistent for these countries.…”
Section: Introductionmentioning
confidence: 99%